Anomalous magnetic behavior of Bi2NiCrO6 nanoparticles with multiferroic behavior synthesized using gel combustion. Issue 3 (15th February 2020) - Ravi, S.; Senthilkumar, C.
Abstract: The Bi2 NiCrO6 double perovskite nanoparticles were synthesized using the gel combustion method. The X-ray diffraction (XRD) results showed a P21/n symmetry with a = 5.5357 Å, b = 5.5522 Å, and c = 7.7204 Å, with β = 90.0031°. The magnetic behavior is anomalous; however, ferromagnetic (FM) ordering was observed at room temperature and at 100 K. Ferroelectric (FE) hysteresis was found for different voltages, which confirms the multiferroic nature of the Bi2 NiCrO6 nanoparticles.